PHYTOSYNTHESIS OF SILVER NANOPARTICLES FROM THE EXTRACTS OF SEAWEED ULVA LACTUCA AND ITS ANTIMICROBIAL ACTIVITY - B. VALENTIN BHIMBA; P. RAJA KUMARI (International Journal of Pharma and Bio Sciences, 2014)
Nanoparticles with controlled size and composition are of fundamental and technological interest as they provide solutions to technological and environmental challenges in the areas of catalysis, medicine, solar energy conversion and water treatment. Thus, production and application of nanomaterials is an emerging field of research. In this present study, silver nanoparticles were synthesized from the aqueous extract of seaweed Ulva lactuca. UV-visible spectroscopy studies were carried out to assess the formation of silver nanoparticles and further characterized by Fourier Transform Infrared spectroscopy (FTIR), X-ray Diffraction (XRD), Thermo Gravimetric Analysis (TGA), EDAX, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) analysis. Further, these synthesized nanoparticles were screened for anti-bacterial and antifungal activity.